2011 IEEE 26th Annual Symposium on Logic in Computer Science 2011
DOI: 10.1109/lics.2011.14
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Two-Variable Dependence Logic and IF-Logic

Abstract: We study the two-variable fragments D 2 and IF 2 of dependence logic and independence friendly logic. We consider the satisfiability and finite satisfiability problems of these logics and show that for D 2 , both problems are NEXPTIME-complete, whereas for IF 2 , the problems are Π 0 1 and Σ 0 1-complete, respectively. We also show that D 2 is strictly less expressive than IF 2 and that already in D 2 , equicardinality of two unary predicates and infinity can be expressed (the latter in the presence of a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…• The Satisfiability problem for the two variable fragment of dependence logic was shown to be NEXPTIME-complete in [15].…”
Section: Introductionmentioning
confidence: 99%
“…• The Satisfiability problem for the two variable fragment of dependence logic was shown to be NEXPTIME-complete in [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, if L=MDL then the satisfiability problem is complete for non‐deterministic exponential time (NEXPTIME) (Sevenster, ). In (Kontinen et al, ), the two‐variable fragment D2 of dependence logic was studied. The two‐variable fragment FO 2 of first‐order logic, and its many extensions, have been widely studied due to their connections to modal logic and to many practical applications.…”
Section: Complexity Results For Dependence Logicmentioning
confidence: 99%
“…While the descriptive complexity of most known logics based on team semantics is understood reasonably well, the complexity of related satisfiability problems has received somewhat less attention. The satisfiability problem of the two-variable fragment of dependence logic and IF-logic have been studied in [18]. It is shown that while the two-variable IF-logic is undecidable, the corresponding fragment of dependence logic is NEXPTIME-complete.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we prove that the validity problem of two-variable dependence logic is undecidable; this result is the main result of the paper. The problem has been open for some time in the team semantics literature and has been explicitly posed in, e.g., [5], [18], [25], and elsewhere.…”
Section: Introductionmentioning
confidence: 99%